The Effect of the CORE Learning Model (Connecting, Organizing, Reflecting, Extending) with Lumio by Smart Media on High School Students' Critical Thinking Abilities and Physics Learning Outcomes - Mariska Yudha Amindri; Singgih Bektiarso; Maryani Maryani; Ike Lusi Meilina (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
Physics learning requires higher-order thinking skills, particularly critical thinking and conceptual understanding. However, students’ critical thinking skills and physics learning outcomes at the senior high school level are still relatively low due to teacher-centered instruction and the limited use of innovative learning models and media. This study aimed to examine the effect of the CORE (Connecting, Organizing, Reflecting, Extending) learning model assisted by Lumio by Smart media on students’ critical thinking skills and physics learning outcomes. This research employed a true experimental design with a post-test only control group design conducted at SMAN 4 Jember in the 2025/2026 academic year. The samples consisted of two classes, with class XI Umum 2 as the experimental class and class XI Teknik 3 as the control class. Data were collected through tests and analyzed using the Mann–Whitney U test. The results showed significance values of 0.027 ≤ 0,05 for critical thinking skills which means H0 is rejected and Ha is accepted and 0.020 ≤ 0,05 for physics learning outcomes which means H0 is rejected and Ha is accepted. Therefore, it can be concluded that the CORE learning model assisted by Lumio by Smart media has a significant effect on students’ critical thinking skills and physics learning outcomes.